Language Skills Competency Required in English Teacher for Realization of Viksit Bharat @ 2047 - Malek, Sabnurbanu Maiyuddin (RESEARCH HUB International Multidisciplinary Research Journal, 2025)
The role of the present teacher has undergone tremendous change, owing to modern technological development. It is necessary and true that a teacher has to be resourceful so that she presents all available knowledge and transfers right information to the students. In child-centered education, the teacher has to initiate his/her students into the art of learning. They have to learn how to learn. Learning to learn is helping the students to acquire the right mental attitude and learning habits. In many ways a teacher can help the child to learn. It is always possible that a child can be trained to develop desirable learning techniques and strategies. This is the responsibility of every teacher and a special responsibility of the language teacher. These techniques and strategies of learning are cold study skills. Learning teaching process is the most effective in teaching the necessary skills in language learning. A language teacher also has the duty to initiate the students into art of learning. Knowledge is a broad term and is available in various ways and in many different types of material. Information when needed can be get from refer to books, journals, articles etc. A student should be familiar with the source of information related to his discipline and as how to retrieve them, store them, etc. This paper focuses on language skills competency required in English teacher for realization of Viksit Bharat @ 2047. This paper also focuses on sub-skills involved in the fundamental skills, meaning and two kinds of listening, meaning and sub-skills of speaking, characteristics of a good oral skills, characteristics of reading and types of reading, steps involved in developing good handwriting and devices for teaching spelling.
Keywords: Language Skills; Competency; English Teacher; Viksit Bharat